Globalisation, environmental crisis, and social change in Bangladesh - Rahamāna, Matiura, 1946- (Dhaka : The University Press Ltd., 2003)
Contributed articles.
Includes statistical tables.
Includes bibliographical references and index.
BIED
Keywords: Globalization -- Economic aspects -- Bangladesh; Globalization -- Social aspects -- Bangladesh; Clothing trade -- Bangladesh -- Statistics; Shrimp industry -- Bangladesh -- Statistics; Bangladesh -- Economic policy; Bangladesh -- Social policy